Programming solutions for machining / Nor Hasnan Hussain and Mat Yudin Juhari - Hussain, Nor Hasnan; Juhari, Mat Yudin (Faculty of Mechanical Engineering, 1986)
We have carried out the preliminary stage of the project entitled ’The Programming Solution for Machining' successfully but there is still room for improvement. The calculation of the tool life for various tool materials under a particular machining conditions have been computerised and this is given in the Section I program. Here we have used the BASIC language. Wo have also computerised the calculation of the total operation time and total parts per hour for the milling operation. Here we have used the program written by Mr. J.E Nicks in his book 'Basic Programming for Manufacturing' as the guideline. This is given in the Section II program.